2021
DOI: 10.3390/agriculture11030194
|View full text |Cite|
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Enhance Soil Key Enzymes, Plant Growth, Seed Yield, and Qualitative Attributes of Guar

Abstract: Guar is an economically important legume crop that is used for gum production. The clean and sustainable production of guar, especially in newly reclaimed lands, requires biofertilizers that can reduce the use of mineral fertilizers, which have harmful effects on human health and the environment. The present study was conducted to investigate the effects of biofertilizers produced from Bradyrhizobium sp., Bacillus subtilis, and arbuscular mycorrhizal fungi (AMF), individually or in combinations, on microbial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…The interaction between AMF and plants can enrich soil resources with essential nutrients that help plants to effectively respond to different environmental factors [ 56 ]. Several studies have reported the effects of environmental factors on the effectiveness of AMF in improvement of plant growth [ 29 ]; since AMF are attached to plant roots, they receive a lower amount of photosynthates under Al stress. The present study reported that mycorrhizal growth markedly decreased in lotus compared with barley under Al stress ( Table 1 ), demonstrating that the impact of Al levels on mycorrhizal growth seems to be dependent on the plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction between AMF and plants can enrich soil resources with essential nutrients that help plants to effectively respond to different environmental factors [ 56 ]. Several studies have reported the effects of environmental factors on the effectiveness of AMF in improvement of plant growth [ 29 ]; since AMF are attached to plant roots, they receive a lower amount of photosynthates under Al stress. The present study reported that mycorrhizal growth markedly decreased in lotus compared with barley under Al stress ( Table 1 ), demonstrating that the impact of Al levels on mycorrhizal growth seems to be dependent on the plant species.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, AMF are effectively used to enhance the biological nitrogen fixation and phosphate solubilization processes in soil and the rhizosphere [ 75 ]. In addition, mycorrhizal inoculation significantly enhanced dehydrogenase activity, which could be attributed to the ability of AMF to improve the physical and chemical properties of soil, especially the soil structure, enhancing the organic matter decomposition and remobilizing nutrients, including nitrogen, in the rhizosphere and soil [ 29 ]. Due to the close connection between Pro and N metabolism [ 68 ], enhanced N uptake could enhance Pro accumulation Pro [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Masciarelli et al (2014) Arbuscular mycorrhizal fungi (AMF) are also able to promote plant nutrients and water uptake as well as increase resistance to several abiotic stresses, especially drought and salinity (Cely et al, 2016;Rathod et al, 2011;Sun et al, 2018). AMF inoculation techniques have been applied in field trials to increase the quantitative and qualitative traits of several field crops (Cely et al, 2016;El-Sawah et al, 2021;Gao et al, 2020). Gholamhoseini et al (2013) reported that AMF symbiosis can alleviate drought stress and increase root size, leaf area, and plant biomass under immediate drought conditions.…”
mentioning
confidence: 99%
“…Two field experiments were conducted during the 2018 and 2019 growing seasons at the Agronomy Farm of Mansoura University, Egypt, from May to November. The meteorological data and the soil properties of the study area were described in our previous studies [29,30]. The experimental plots comprised four ridges of 3.5 m in length; the spacing between ridges was 70 cm and between hills was 25 cm.…”
Section: Experimental Site Plant Materials and Agronomic Practicesmentioning
confidence: 99%